Religion and sexuality in Brazil: technologies of si and the eu in the discursive historicity of the construction of the brazilian subject - Souza Monteiro, Solange Aparecida de; Momesso, Maria Regina; Delgado, Monique; Marçal Ribeiro, Paulo Rennes (Laboratório Editorial Faculdade de Ciências e Letras, 2019)
The objective is to reflect the theme of sexuality from the discursive/historical construction of its control mechanisms by institutions, especially religious ones. In a linear way, the history of sexuality from antiquity stands out: on the one hand, the East, where sexuality was perceived as spiritual enlightenment, on the other, the West, especially the classical Greco-Roman philosophy, which accepted it, without a moralistic imposition, but pleasure should be ruled. In the Middle Ages, from Christianity, sexuality becomes understood and discursivized as a sin. In this period stands out the influence of the medieval worldview definitively on our sexual morals. Finally, in the history of Brazil, religion has an influence on sexual morality already from the colonization and Jesuit indoctrination to the official positions of the current religions on sexuality, especially the position of the Catholic Church, with Pope Benedict XVI. From this look at discursive historicity, it is also intended to investigate to what extent it is possible to develop a theological understanding that has as its presupposition the approach on the techniques of himself and the technologies of the self undertaken by Michel Foucault in his last phase, especially in his work A hermeneutics of the subject.